The pen for the sword: how the end of the Second Boer War unified Afrikaner culture and led to Afrikaner political dominance in South Africa - Suttle, Timothy Evan Thomas (Kansas State University, 2018)
The end of the Second Boer War in 1902 gave rise to cultural and political action of Afrikaners within the colonial governments and among the South African people. These actions caused a rise in Afrikaner cultural and political nationalism. Though the British emerged victorious from the war, resentment for the British Empire was widespread in the South African colonies due to brutalities suffered by the Afrikaners during the war. This resentment would later be channeled by Afrikaner leaders and used as a political weapon. The British wished for appeasement with the Afrikaners and established terms at the end of the war that Afrikaner leaders were able to use to further Afrikaner culture through politics. The military victory for the British influenced many Afrikaners to trade violence for political and cultural means of resistance. Throughout the years 1902-1924 the Afrikaner people established strategies through politics, literary publications, and new political groups, developed in the years 1904-1908, to advocate for Afrikaner nationalism and cultural equality amongst the British in areas of law, commerce, and education. The war showed the futility of military resistance against the British, but inspired many to push for political and cultural resistance, unification, and eventual dominance. Afrikaner nationalist dominance in South Africa began with the efforts of the Afrikaner leaders and people in 1902 after the Second Boer War.
Keywords: Postwar Afrikaner political and cultural nationalism